Лучшие рефераты по управленческому учету, финансам и кредиту: учебное пособие / отв. ред.: Ж Фролова, О Морозова - Фролова Жанна (Банк Рефератов, 2002)
Экземпляры: (20180329) / Инвентарный номер: 2139 / Цена: / Сис.шифр: 65.9(2)26 / Авт.знак: Л87 / ГРНТИ: 06.73 / ББК: 65.9(2)26 я73